Graphite Lithium‐Ion Cells: On the Beneficial Impact of Li2CO3 as Electrolyte Additive in NCM523 ∥ Graphite Lithium Ion Cells Under High‐Voltage Conditions (Adv. Energy Mater. 10/2021). Issue 10 (11th March 2021) - Klein, Sven; Harte, Patrick; Henschel, Jonas; Bärmann, Peer; Borzutzki, Kristina; Beuse, Thomas; van Wickeren, Stefan; Heidrich, Bastian; Kasnatscheew, Johannes; Nowak, Sascha; Winter, Martin; Placke, Tobias
Abstract : In article number 2003756, Martin Winter, Tobias Placke, and co‐workers address challenges related to the high‐voltage operation of NCM523 ‖ graphite lithium‐ion cells, suffering from transition metal (TM) dissolution/deposition, which subsequently induces capacity fading. The use of Li2 CO3 as an electrolyte additive can significantly improve the capacity retention by in situ formation of 'scavenging' agents for TMs, thus, preventing TM deposition at graphite.